Bi-relaxation behaviors in epitaxial multiferroic double-Perovskite BiFe0.5Mn0.5O3/CaRuO3 heterostructures - Chew, Khian Hooi; Jiang, Y.; Miao, J.; Zhang, X.; Zhan, Q. (AIP Publishing, 2011)
Multiferroic double-perovskite BiFe0.5Mn0.5O3 thin film heterostructures were epitaxially grown on CaRuO3-buffered (001) SrTiO3 by pulse laser deposition. Typical Vogel-Fulcher relaxorlike dielectric and magnetic susceptibilities were observed, implying the film exhibits the properties of an electric relaxor and a magnetic relaxor. Polarization and size of polar nanoregions (PNRs) were determined by fitting the dielectric constant to a multi-polarization mechanism model. It was found that PNRs of 7-11 nm decrease from 0.67 mu C/cm(2) to 0.11 mu C/cm(2), as the temperature increases from 380 K to 460 K. A weak ferromagnetism was observed via magnetic hysteresis loops up to 300 K. (C) 2011 American Institute of Physics. [doi:10.1063/1.3624847]